2011
DOI: 10.1111/j.1708-8208.2011.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of an Implant Impression Technique Using Digitally Coded Healing Abutments

Abstract: Both conventional and robot technique presented low levels of displacement of the implant analogues in all casts. The test technique was less precise, but the difference in accuracy was small, and both techniques are precise enough for single crowns and short-span, implant-supported fixed partial prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 16 publications
1
42
0
3
Order By: Relevance
“…40 In some studies the authors express the opinion that the results were not more favorable for the CAD/CAM groups due to the inaccuracies of impression making and cast fabrications, and found the intraoral impression devices as a very promising approach. 41,16 LEGENDS Fig.1. Baseline of the prosthetic phase, two and a half months after the surgery.…”
Section: Cad/cammentioning
confidence: 99%
See 1 more Smart Citation
“…40 In some studies the authors express the opinion that the results were not more favorable for the CAD/CAM groups due to the inaccuracies of impression making and cast fabrications, and found the intraoral impression devices as a very promising approach. 41,16 LEGENDS Fig.1. Baseline of the prosthetic phase, two and a half months after the surgery.…”
Section: Cad/cammentioning
confidence: 99%
“…3 Several implant impression studies have reported that working casts fail to exactly replicate the original situation. 16,17 The introduction of computer-aided design/Computer aided manufacturing (CAD/CAM) technology in dentistry has resulted in a more accurate manufacturing of prosthetic frameworks, greater accuracy of dental restorations and implant supported prosthesis in particular 18 .…”
Section: -2mentioning
confidence: 99%
“…Although practical evidence is limited, theoretically these successive unions of clouds of points could cause an accumulation of error. For this reason, reliability diminishes progressively according to the increasing number of implants analyzed (25). But in contrast with intraoral video and photographic scanners, photogrammetry generates director vectors of the exact position of the implants in relation to one another.…”
Section: Discussionmentioning
confidence: 99%
“…Eliasson i wsp. 68 do badania użyli specjalnych śrub goją-cych z systemu Encode (Biomet 3i), które skanowali skanerem stołowym (3shape). Wyniki tych badań wykazały, że techniki cyfrowe są mniej dokładne od technik klasycznych.…”
Section: Digitalizacja Wycisku -Wyciski Cyfroweunclassified